Defining the objectives of a center improvement plan - Polo Martínez, Ignacio; Puertas Bescós, Gemma (Avances en Supervisión Educativa, 2024)
The future of school management appears to be decisively moving towards accountability. This is not good or bad; it is just needed. LOMLOE has detected this gap in school management and requires the need for every educational project to include an improvement plan that involves the school community. With this involvement, teachers and, especially, principals have a decisive role. They have the responsibility to define the objectives and the actions required to raise the achievement level of each. These objectives should be identified with initial data, setting a target achievement level for each within a specified period of time. The objectives included in the improvement plan should contain three fundamental variables: the improvement of educational results (both curricular and in terms of school climate), the coordination of teaching processes (both internal and with other affiliated schools), and family involvement. Relevant changes in any of these three variables will only be achieved if the school principal, starting from a solid plan, engages the school community in daily improvement efforts. Among the involved participants, although all are important, teachers will play a main role.